Challenges Faced by Start-up Non-Profit Organisations in South Africa - McIntyre, Cailley (Department of Social Development, 2022)
This research study explores ‘Challenges faced by Non-Profit Organisations in South Africa'. The study was informed by a qualitative approach and an exploratory design. Face-to-face interviews were conducted to collect the data, with participants selected from twenty purposively sampled NPOs. A semi-structured interview schedule was utilised and data was analysed using Tesch's (1990) process for data analysis. Ethical clearance was received from the Department of Social Development at the University of Cape Town. The research study found that NPOs do face a number of challenges that are prevalent in their start-up phase, relating to organisation leadership, financial sustainability and resource management. Organisation leadership challenges revolve around a lack of leadership, knowledge, experience and/or skill; managing and monitoring service delivery; the impact of the pressure to survive; and growth complications. Challenges in terms of financial sustainability and navigating the funding landscape pertain to are donor attraction; fundraising knowledge; donor relationships and the power dynamics; donor perceptions; the impact of sources of funding; and the influence of immediate survival needs on long-term planning and sustainability. Resource management is also a challenge in terms of physical and human resources, such as staffing, role ambiguity, cost of salaries and the effect of reliance on alternative streams of income, the tension between the finances available and the quality and/or experience of the person that the NPO is able to afford, and the impact of high staff turnover. Any one of these challenges can cause start-up NPOs to become vulnerable, unsustainable and likely to fail. The contribution that this study makes to knowledge building is an enhanced evaluation of the challenges that NPOs face in South Africa, and the factors that they may employ to mitigate these challenges and increase their likelihood of success. It recommends practical alternatives to the way that NPOs operate in terms of organisational leadership and financial sustainability, that may improve their chances of survival and success. The main recommendations talk to the need for consulting, in-depth reviewing of the NPO landscape, partnerships and collaboration, and financial self-sufficiency.